Toward a Taxonomy of Climate Emotions - Pihkala, Panu (Frontiers in Climate, 2022)
There is a growing evidence that emotions shape people’s reactions to the climate crisis in profound but complex ways. Climate emotions are related to resilience, climate action, and psychological well-being and health. However, there is currently a lack of research about the array of various climate emotions. There is also a need for more integration with general research about emotions. This article conducts a preliminary exploration of the taxonomy of climate emotions, based on literature reviews and philosophical discussion. The term emotion is used here in a broad sense, as is common in climate emotion research. Because of the urgency of the climate crisis and the lack of previous research, this kind of exploration is aimed to be helpful for both practical climate work and for future research which would include more systematic reviews of the topic. Research items which discuss at least five different climate emotions, based on empirical observations, are used as major sources and a table about them is provided. Climate emotions are discussed on the basis of interdisciplinary research. The article considers many aspects of the phenomena of climate anxiety and climate grief.